PENGARUH BUDAYA ORGANISASI TERHADAP EFEKTIVITAS PENERAPAN AKUNTANSI SEKTOR PUBLIK SERTA DAMPAKNYA TERHADAP GOOD GOVERNANCE - Funi Suci Ramadan; Anik Malikah; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2021)
This research was conducted by researchers with the aim and purpose of being able to determine the direct or indirect influence between the influence of organizational culture on the effectiveness of the implementation of public sector accounting and its impact on good governance in the Environmental Service of Malang City. Data analysis and hypothesis testing were carried out using Path Analysis. The population obtained in the study was 50 respondents with a sample of 30 respondents. In this study, data collection was carried out using questionnaires or questionnaire instruments. The results of the study indicate that: (1) Organizational Culture has a significant effect on the Effectiveness of Public Sector Accounting Implementation and the amount of influence is in the medium category. This shows that organizational culture has contributed significantly in increasing the effectiveness of the implementation of public sector accounting but has not yet reached the expected maximum level. (2) Effectiveness of Public Sector Accounting Implementation has a significant effect on Good GovernanceKeywords: Organizational Culture, Effectiveness of Public Sector Accounting Implementation, Good Governance.